If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -7) = 5(x + 3) Reorder the terms: 3(-7 + 2x) = 5(x + 3) (-7 * 3 + 2x * 3) = 5(x + 3) (-21 + 6x) = 5(x + 3) Reorder the terms: -21 + 6x = 5(3 + x) -21 + 6x = (3 * 5 + x * 5) -21 + 6x = (15 + 5x) Solving -21 + 6x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -21 + 6x + -5x = 15 + 5x + -5x Combine like terms: 6x + -5x = 1x -21 + 1x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 -21 + 1x = 15 + 0 -21 + 1x = 15 Add '21' to each side of the equation. -21 + 21 + 1x = 15 + 21 Combine like terms: -21 + 21 = 0 0 + 1x = 15 + 21 1x = 15 + 21 Combine like terms: 15 + 21 = 36 1x = 36 Divide each side by '1'. x = 36 Simplifying x = 36
| 10=c/3-4+c/6 | | 3m-6+2m=9 | | 16+-5= | | 2(a+4)=2(a+4)+4a | | 60x=90 | | 4x+(-6x)=10 | | -4(5x+7)=12 | | 0=-2x+19x+33 | | 23-3x=-4(7x+4)-4(-5-6x) | | 5x-7=2x+20 | | 0.6m=0.5 | | X^2+26x+120=2x^2 | | 7z+3=7z-z | | 12x+18=36 | | 14x+88(56)=12 | | 5x+9+x=69 | | -16+5x=42+-56x+3 | | 14x+88(56)= | | 2(4(3)-3)-8=4+2(3) | | 7-(-9+2i)-(-17-i)= | | 3x+10+4x=45 | | 1=-2-(4-x) | | 16+2x=5x+10 | | x^2-6x+5-2x=5 | | 4(x+5)=6(2x-2) | | 7a+12b-8a= | | 12y^2-48y=0 | | 3x-7+6x=20 | | -8n-4n+5= | | 2-0.6(f-1)=0.2(7f-1) | | 24x+8x-48x=4x-3 | | 23-3x=-4(7x+4)-4(5-6x) |